Who Is Treating Periprosthetic Femur Fractures? An Analysis of the Periprosthetic Research Consortium - Nicholas B. Pohl, MS; Arjun Saxena, MD, MBA; Jeffrey B. Stambough, MD; John Ryan Martin, MD; Simon C. Mears, MD, PhD; Paul M. Lichstein, MD, MS; Eric Jordan, BS; Cameron R. Egan, MD; Antonia F. Chen, MD, MBA; Greg A. Erens, MD; Samir Chabib, MD; Bryce Wall, MD; et al. (Arthroplasty Today, 2024)
Background: Periprosthetic femur fractures (PPFFs) following total hip arthroplasty (THA) have increased in the past decade as the demand for primary surgery continues to grow. Although there is now more evidence to describe the treatment of Vancouver B fractures, there is still limited knowledge regarding factors that cause surgeons to perform either an open reduction and internal fixation (ORIF) or revision THA (rTHA). The purpose of this study was to determine what type of surgeons treat Vancouver B PPFFs at 11 major academic institutions and if there are trends in treatment decision-making regarding the use of ORIF or rTHA based on surgical training or patient factors. Methods: This multicenter retrospective study evaluated patients surgically treated for Vancouver B PPFF after THA between 2014 and 2019. Patients from 11 academic centers located in the United States were included in this study. Surgical outcomes and patient demographics were evaluated based on surgeon training, surgical treatment type, and institution. Results: Presence of Vancouver B2 (odds ratio [OR]: 0.02, P < .001) or B3 (OR: 0.04, P < .001) fractures were independent risk factors for treatment with rTHA. Treatment by a trauma (OR: 12.49, P < .001) or other-specified surgeon (OR: 13.63, P < .001) were independent risk factors for ORIF repair of Vancouver B fractures. There were no differences in outcomes based on surgeon subspecialty training. Conclusions: This study showed the trends in surgeons who surgically manage Vancouver B fractures at 11 major academic institutions and highlighted that regardless of surgical training or surgical treatment type, postoperative outcomes following management of PPFF were similar.